Effects of empagliflozin in patients with chronic kidney disease from Japan: exploratory analyses from EMPA-KIDNEY - Nangaku, Masaomi; Herrington, William G.; Goto, Shinya; Maruyama, Shoichi; Kashihara, Naoki; Ueki, Kohjiro; Wada, Jun; Watada, Hirotaka; Nakashima, Eitaro; Lee, Ryonfa; Massey, Dan; Mayne, Kaitlin J.; et al. (Clinical and experimental nephrology, 2024)
EMPA-KIDNEY assessed the effects of empagliflozin 10 mg once daily vs. placebo in 6609 patients with chronic kidney disease (CKD) at risk of progression, including 612 participants from Japan.